MODERASI PENDIDIKAN ISLAM DI INDONESIA - Madian; Mujib, Ahmad (Journal of Islamic Education Studies, 2022)
Moderation in Islamic education is indispensable in the world of education in Indonesia for the sake of creating a democratic educational atmosphere. This study uses a descriptive qualitative method with a literature study approach. Research data is taken directly from various main sources in the form of relevant articles, journals and books. The data that has been collected is then analyzed descriptively. This study concludes that moderation of Islamic education is education that carries Islamic values that can be accepted by all groups by applying the values of tawasuth, tawazun, i'tidal, tasamuh, musaawaah, shura, islah, awlawiyah, tathawur wa ibtikar, tahaddhur, tanawwu' and uswah. The supporting aspects are school policies, materials and learning, education staff, parents and teachers. It is carried out by democratizing Islamic education which builds an education system that is centralized, uniform, and dependent, to shift to developing a more autonomous, diverse, and independent education system. The success of Islamic education moderation can be seen in the positive changes of each individual, living environment and interactions between communities.